2022
DOI: 10.1002/rcr2.1012
|View full text |Cite
|
Sign up to set email alerts
|

Severe and critical SARS‐COV‐2 delta variant infection in infants without underlying medical conditions

Abstract: We report herein a case series of infants, with no comorbidities, who developed a life‐threatening illness due to the SARS‐CoV‐2 Delta variant. We retrospectively reviewed the medical records of children, aged under 15 years, admitted to PICU, during the peak of Delta infection, between June 23 and August 16 2021, with severe and critical forms of SARS‐CoV‐2 infection, confirmed by RT‐PCR. Twenty infants were included, the median age was 47 days (IQR: 26.5–77) and sex ratio was 0.8. No underlying medical condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Findings implied that the higher hospitalization rates seen with the emergence of Delta were not a result of increased pathogenicity of the variant but simply due to the increased prevalence of infection. However, a case series in Tunisia reported that Delta causes critical outcomes in infants (<2 years) without any underlying conditions whose mothers were unvaccinated, where over half of the patients had pediatric ARDS and 20% ended with death ( 46 ). While this is not an overarching outcome of all pediatric SARS-CoV-2 infections, it emphasizes the potential risk new variants could bring.…”
Section: Pediatric Responses To Sars-cov-2 Variantsmentioning
confidence: 99%
“…Findings implied that the higher hospitalization rates seen with the emergence of Delta were not a result of increased pathogenicity of the variant but simply due to the increased prevalence of infection. However, a case series in Tunisia reported that Delta causes critical outcomes in infants (<2 years) without any underlying conditions whose mothers were unvaccinated, where over half of the patients had pediatric ARDS and 20% ended with death ( 46 ). While this is not an overarching outcome of all pediatric SARS-CoV-2 infections, it emphasizes the potential risk new variants could bring.…”
Section: Pediatric Responses To Sars-cov-2 Variantsmentioning
confidence: 99%